PP.01.38: IMPACT OF SHORT-TERM EXERCISE TRAINING ON ARTERIAL BLOOD PRESSURE, DOUBLE PRODUCT AND QT DISPERSION IN PATIENTS AFTER MYOCARDIAL INFARCTION. (June 2015) - Stoickov, V.; Ilic, M. Deljanin; Ilic, S.; Stoickov, M.; Saric, S.; Petrovic, D.; Nikolic, L.; Cvetkovic, J.; Andonov, S.
Abstract : Objective: The aim of this study was to establish the influence of short-term exercise training on arterial blood pressure (BP), double product (DP) and corrected QT dispersion (QTdc) in diabetic patients after myocardial infarction (MI). Design and method: The study involved 375 patients after MI (mean age 57.1 years). Patients were randomly divided into the physical training group (TG: 333 patients) and non-training group (NTG: 42 patients). Diabetes was present in 107 (32.1 %) patients in the TG and in 14 (33.3 %) patients in the NTG. In all subjects exercise test were performed and after that TG patients were included in rehabilitation treatment for three weeks. TG patients were instructed to follow a training program using the bicycle ergometer (10 min, 2 times a day) and walking. The patients continued to take the same medicaments in same doses. Results: Before starting with the program of physical training, TG patients with diabetes had significantly higher values of QTdc (81.4 ± 25.9 vs 68.9 ± 23.4 ms; p < 0.001), while the values of DP, systolic and diastolic BP did not significantly vary in comparison to those without diabetes. After three weeks in the TG patients with diabetes, we have found significant reduction of systolic BP from 138.2 ± 13.4 to 131.7 ± 11.8 mmHg (p < 0.001), of diastolic BP from 87.0 ± 7.8 to 83.8 ± 8.2 mmHg (p < 0.005), of DP from 12203.7 ± 1962.2 to 11463.1 ± 1700.8 beat/min x mmHg (p < 0.005), of QTdc from 81.4 ± 25.9 to 73.8 ± 24.1 ms (p < 0.02) and of glycemia from 8.2 ± 3.2 to 7.2 ± 1.9 mmol/L (p < 0.005). In TG patients without diabetes, after three weeks, we have found significant reduction of systolic BP from 137.8 ± 12.3 to 128.5 ± 10.1 mmHg (p < 0.001), of diastolic BP from 86.8 ± 7.4 to 81.4 ± 5.6 mmHg (p < 0.001), of DP from 12011.4 ± 1897.3 to 11073.8 ± 1551.6 beat/min x mmHg (p < 0.001) and of QTdc from 68.5 ± 23.4 to 56.9 ± 20.6 ms (p < 0.001). In contrast, the NTG showed no significant changes. Conclusions: The study showed that short-term exercise training has favourable effects on arterial BP, DP and QTdc in patients after MI, especially in those without diabetes. Physical training led to the significant decrease of myocardial oxygen uptake at rest and probably decreased the possibility of arrhythmia events.